East of Wall [videorecording (DVD)] - Beecroft, Kate; Zimiga, Tabatha; Zimiga, Porshia; McNairy, Scoot; Ehle, Jennifer, 1969-; Blackaller, Christina; Frank, Lukas (Composer); Meyer-O'Keefe, Daniel; Vecchiarello, Jennifer, 1983-; Shelton, Austin (Sony Pictures Home Entertainment, 2025)
"East of Wall is an authentic portrait of female resilience in the 'New West,' inspired and played by the women and girls who live it. Set in the Badlands of South Dakota, Tabatha, a young, rebellious rancher, who rescues and resells horses, must make hard decisions to deal with her fractured family, financial uncertainty, and unresolved grief, all while providing refuge for a group of wayward neighborhood teens."--